0969 Early Life Sleep Disturbance Among Children With Autism Spectrum Disorders: A Questionnaire-based Retrospective Study. (27th May 2020) - Gupta, A; Shukla, G; Poornima, S; Mohd, A; Katoch, J; Taneja, D; Singhal, N
Abstract: Introduction: Autism spectrum disorders(ASD) and sleep has hand to hand relationship and few recently published studies have shown that, disturbed infant sleep is associated with Attention deficit hyperactive disorder and Autism. The aim of the study is to evaluate the sleep disturbance in first year of life among the children with ASD. Methods: In this case control study, pre-diagnosed ASD children between 3-12 year of age (group 1) and controls; sibling of autistic children and community dwelling children(group 2), were enrolled in between June 2014 to November 2017. After giving consent every child underwent, Detailed Clinical [Childhood Autism rating scale-2(CARS-2)] and Sleep evaluation [Brief Infant sleep Questionnaire (BISQ) - Retrospectively, Child sleep habits questionnaire (CSHQ)]. Results: Sixty children in group1 and 60 in group 2 were enrolled and both groups were age [Median 7(2.5-12) vs. 8.5 (2.5-12), p = 0.14] and sex [53(88.33%) vs. 45(75.00 %), p=0.15] matched. On CHSQ poor sleepers are more common among the group 1[40(66.66%) vs. 20(33.33%), p=.003, respectively]. On BISQ children had severe sleep problems during infancy were significantly more among the group 1 [46(76.66%) vs. 6(10%), p=<.001, respectively]. Duration of nocturnal awakening was significantly correlated (r=0.87, p=.001) with the T score of the CARS-2. Conclusion: Sleep is significantly disturbed since infancy among children with autism spectrum disorder and duration of nocturnal awakenings during infancy is strongly correlated with severity of autism. Support: NA